2010
DOI: 10.1108/02683941011023712
|View full text |Cite
|
Sign up to set email alerts
|

Justice perceptions of performance appraisal practices

Abstract: Purpose -The purpose of this paper is to explore the underlying structure of employees' justice perceptions in the context of their organizations' performance appraisal practices. Design/methodology/approach -Ten multi-item scales were designed to measure the perceived fairness of performance appraisal practices. A nested confirmatory factor analysis of employee responses (n ¼ 188) compared the four justice dimensions (i.e. procedural, distributive, interpersonal, informational) to five plausible alternatives.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
131
0
27

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(165 citation statements)
references
References 35 publications
7
131
0
27
Order By: Relevance
“…These include goal acceptance and commitment, goal specificity, goal difficulty, and feedback. These conditions have been extended and edited by other researchers, such as Kenneth Blanchard and Spencer Johnson's SMART goals, which are conditions that are necessary to make goals effective (Thurston & McNall, 2010).…”
Section: Goal Setting Theorymentioning
confidence: 99%
“…These include goal acceptance and commitment, goal specificity, goal difficulty, and feedback. These conditions have been extended and edited by other researchers, such as Kenneth Blanchard and Spencer Johnson's SMART goals, which are conditions that are necessary to make goals effective (Thurston & McNall, 2010).…”
Section: Goal Setting Theorymentioning
confidence: 99%
“…The Cronbach's alpha was calculated for each construct to determine the scale reliability. Thurston and McNall (2010) reported that Cronbach's alpha should range from the lowest of 0.68 and to the highest of 0.93. The Total Rewards Scale results (0.822).…”
Section: Ethical Consideration and Research Proceduresmentioning
confidence: 99%
“…This factor suggests that employee performance can be evaluated through multiple sources such as supervisors, managers, self, peers and even customers (Wood and Marshall, 2008). Another important characteristic of performance appraisal is the purpose for which performance has been appraised or evaluated (Thurston, 2001), and typically, performance appraisal systems are utilized for multiple purposes ranging from developmental and administrative purposes. Feedback richness is also an effective indicator that may affect the outcomes of performance appraisal.…”
Section: Literature Reviewmentioning
confidence: 99%